Food insecurity and domestic instability: a review of the literature - Rudolfsen, Ida (Terrorism and political violence, 2020)
Research on the relationship between food insecurity and unrest has a long history. The food price spikes in 2007–2008 and 2010–2011 coincided with demonstrations and incidents of large-scale violence, prompting renewed scholarly interest in the link between food insecurity and unrest. This paper reviews the literature, synthesises its main empirical findings and central explanations, and identifies four particular issues to consider to enhance our understanding of how food insecurity is related to unrest. First, there is a wide range of suggested theoretical mechanisms of how food insecurity is linked to unrest, but the empirical tests are akin. Second, there exist various notions of the independent variable, but there is a gap between the theoretical definition and measurement. Third, the focus is often on “food riots”, but whether rioting is the most likely response, and whether it is possible to separate between “food-related” unrest and other types of turmoil is unclear. Lastly, there is a challenge to address the endogenous nature of food insecurity and unrest. The paper adds to the literature by pointing to the theoretical mechanisms linking food insecurity to unrest, relating both to the type and degree of food insecurity, and how we understand and define unrest.